2015
DOI: 10.1177/070674371506000609
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy in Contemporary Psychiatric Practice

Abstract: Objective: American data suggest a declining trend in the provision of psychotherapy by psychiatrists. Nevertheless, the extent to which such findings generalize to psychiatric practice in other countries is unclear. We surveyed psychiatrists in British Columbia to examine whether the reported decline in psychotherapy provision extends to the landscape of Canadian psychiatric practice. Method:A survey was mailed to the entire population of fully licensed psychiatrists registered in British Columbia (n = 623). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…There is enough evidence that psychotherapy treatment effects for most disorders are equivalent to or stronger than those of psychopharmacology [33]. A study reported about 81% psychiatrists in British Columbia continuing to integrate psychotherapy and pharmacotherapy in clinical practice [34]. While the proportion of time spent by psychiatrists practicing psychotherapy has diminished steadily over recent decades, the extent of this decline in non-English speaking countries is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There is enough evidence that psychotherapy treatment effects for most disorders are equivalent to or stronger than those of psychopharmacology [33]. A study reported about 81% psychiatrists in British Columbia continuing to integrate psychotherapy and pharmacotherapy in clinical practice [34]. While the proportion of time spent by psychiatrists practicing psychotherapy has diminished steadily over recent decades, the extent of this decline in non-English speaking countries is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In communication with individuals affected by mental disorders and with their families/caregivers a set of basic ethical principles should be accomplished (Table 1), namely: respect of patients' autonomy, dignity, opinions, values, privacy and confidentiality, granting honesty and clarity, and tolerance of overt emotions' expression [4,21,[25][26][27][28]. Using an age and culture sensitive language, we should avoid time constraints which are among the worst enemy of communication and one of the most significant obstacles to "patient-centered psychiatry" [29], "shared decision making" [30], and to the implementation of psychotherapy [31], but several specific aspects should be specifically considered. The present paper aims to address ethical issues emerging in communication with patients and families in particular situations and contexts of psychiatric practice.…”
Section: Introductionmentioning
confidence: 99%
“…Today's technology allows trainees to reach various psychotherapeutic training availabilities, including online tools (Webinar, MOOCs, online guidebooks) and international courses. It is advisable that training institutions devote more time on psychotherapy training and supervision, associations provide costly training availabilities or scholarships, encourage more scientific research on psychotherapeutics and take into account the progress of research in psychology and neuroscience [1][2][3][4][5].…”
mentioning
confidence: 99%